The complete mitogenome of the granular torrent frog, Amolops granulosus (Anura: Ranidae) - Huang, An (Mitochondrial DNA B Resour, 2019)
We obtained the complete mitochondrial genome of Amolops granulosus, which was 17,785 bp in length and it contained the 37 typical mitochondrial genes: 2 ribosomal RNAs, 22 transfer RNAs (tRNAs), 13 protein-coding genes (PCGs), and 1 control region (CR). The hotspot of gene arrangement was ranged as ‘W-gap-O(L)-gap-A-N-gap-C-Y’ which consisted with most published Amolops mitogenomes. Our phylogenetic results suggested the gene arrangement of ‘WANCY’ region can facilitate to distinguish the Amolops species as an efficient genetic marker.